Validation of the Comprehensive Feeding Practices Questionnaire among parents of 5- to 7-year-old children in Sweden - Morris, Zoë; Norman, Åsa; Elinder, Liselotte Schäfer; Patterson, Emma; Warnqvist, Anna; Raposo, Sara; Sidney Annerstedt, Kristi (Frontiers in Psychology, 2023)
Parents’ behaviours towards food and mealtimes, also known as parental feeding practices, are important in the development of children’s eating habits. The Comprehensive Feeding Practices Questionnaire (CFPQ) was designed to measure parental feeding practices. The aim of this study was to evaluate the validity of the CFPQ in Sweden and to assess how it performs across different groups of people. Methods: Data were from the baseline of a trial promoting children’s healthy dietary and physical activity behaviours, the Healthy School Start Plus intervention, conducted in 17 schools in the Stockholm region in Sweden. The CFPQ was completed by 263 parents (59% mothers) of 173 children, aged five to seven years. Exploratory factor analysis and the omega reliability test were performed to identify the underlying factors in the data. Invariance testing was used to investigate the equivalence of these factors across parental sex, parental education and children’s weight status. Results: Five factors were identified: monitoring of children’s food intake, pressure to eat, restriction of food, use of food for emotional regulation, and healthy eating guidance. All five factors were invariant across parental sex and education, though some questions were excluded to achieve invariance. The monitoring, pressure to eat and emotional regulation factors were invariant across children’s weight status. Discussion: These results suggest that the CFPQ is valid for use in Sweden, amongst parents of children aged five to seven years. The measurement invariance allows for comparisons of all five underlying factors across mothers and fathers and parental education levels, though across children’s weight status for only three factors. Due to the importance of parental feeding practices throughout childhood, this questionnaire should also be validated in other age groups in Sweden.